Effects of temperature and ambient pressure on the resistive switching behaviour of polymer-based atomic switches. Issue 22 (14th June 2015) - Mohapatra, Saumya R.; Tsuruoka, Tohru; Krishnan, Karthik; Hasegawa, Tsuyoshi; Aono, Masakazu
<x xml:space="preserve">Abstract</x> Effects of temperature and ambient pressure on the resistive switching behavior of electrochemical 'atomic switches' based on pure PEO and Ag-doped PEO were investigated.